Evidence for action: A One Health learning platform on interventions to tackle antimicrobial resistance - Wernli, D.; Jørgensen, P.S.; Parmley, E.J.; Troell, M.; Majowicz, S.; Harbarth, S.; Léger, A.; Lambraki, I.; Graells, T.; Henriksson, Patrik J.G.; Carson, C.; Cousins, M.; et al. (Elsevier, 2020)
Improving evidence for action is crucial to tackle antimicrobial resistance. The number of interventions for antimicrobial resistance is increasing but current research has major limitations in terms of efforts, methods, scope, quality, and reporting. Moving the agenda forwards requires an improved understanding of the diversity of interventions, their feasibility and cost–benefit, the implementation factors that shape and underpin their effectiveness, and the ways in which individual interventions might interact synergistically or antagonistically to influence actions against antimicrobial resistance in different contexts. Within the efforts to strengthen the global governance of antimicrobial resistance, we advocate for the creation of an international One Health platform for online learning. The platform will synthesise the evidence for actions on antimicrobial resistance into a fully accessible database; generate new scientific insights into the design, implementation, evaluation, and reporting of the broad range of interventions relevant to addressing antimicrobial resistance; and ultimately contribute to the goal of building societal resilience to this central challenge of the 21st century.